1001 Beds - Miller, Tim (The University of Wisconsin Press, 2023)
For a quarter century, Tim Miller has worked at the intersection of performance, politics, and identity, using his personal experiences to create entertaining but pointed explorations of life as a gay American man–from the perils and joys of sex and relationships to the struggles of political disenfranchisement and artistic censorship. This intimate autobiographical collage of Miller’s professional and personal life reveals one of the celebrated creators of a crucial contemporary art form and a tireless advocate for the American dream of political equality for all citizens. Here we have the most complete Miller yet–a raucous collection of his performance scripts, essays, interviews, journal entries, and photographs, as well as his most recent stage piece Us. This volume brings together the personal, communal, and national political strands that interweave through his work from its beginnings and ultimately define Miller’s place as a contemporary artist, activist, and gay man.